BACTERIAL DECOLORIZATION OF ACID YELLOW DYE OBTAINED FROM TEXTILE INDUSTRY EFFLUENTSc - K. D. KAMBLE; M. A. MORE (International Journal of Pharma and Bio Sciences, 2013)
Dyes are threat to aquatic as well as human life. These are often introduced in the water bodies from textile or paper industries with improper treatment. Chemical treatments for dye decolorization are quite costly; another disadvantage is decolorization of these dyes is not complete. The bacterial flora in the effluent of textile industries is continuously exposed to dyes. Few of this might be excellent dye decolorizers and also dyes are used as source of carbon and nitrogen by few bacteria. The bacterial decolorization of dyes is preferable one because the dyes are completely decolorized by these bacteria. The case study was carried by selecting acid yellow dye. The efficient dye decolorizing bacteria includes Pseudomonas sp, Alteromonas sp, Enterococcus sp, Serratia sp and Enterobacter sp. Periodic studies on utilization of these dyes are carried out. Dye decolorization was at peak level towards the end of second day. Hence this also suggest when a suitable strategy is developed for the decolorization of dyes two day period will be sufficient to treat the effluent by these bacteria.